Before the “Ecologically Noble Savage”: Gendered representations of Amazonia in the global media in the 1970s - Sarzynski, Sarah (Latin American Perspectives, 2021)
An analysis of media representations of the Amazon and indigenous peoples reveals how media producers and filmmakers foregrounded discourses naturalizing gendered and racialized differences that distinguished the Amazon from the West in the 1970s, a decade during which the Brazilian military dictatorship promoted development projects in Amazonia. These representations often sexualized indigenous peoples and the Amazon itself, portraying them as primitive, cannibal savages, animals or part of nature, or victims of exploitation. The “Othering” of the Amazon and Amazonians was further elaborated through a discourse of binary oppositions that portrayed Western white men as explorers and exploiters who dominated the screen, scripts, studies, and development projects even if they were doomed to fail. By relying on a symbolic system of difference, global media coverage and films about Amazonia in the 1970s were complicit in legitimizing authoritarian decrees promoting large-scale development that depicted indigenous peoples and the environment as obstacles. Un análisis de las representaciones mediáticas de la Amazonía y sus pueblos indígenas revela cómo, en la década de 1970, productores y cineastas mediáticos resaltaron discursos que naturalizaron las diferencias de género y racializadas con las que se distinguían a la Amazonía del Occidente en una época durante la cual la dictadura militar brasileña promovió proyectos de desarrollo en la región. Dichas representaciones a menudo sexualizaban a los pueblos indígenas y a la Amazonía misma, retratándolos como primitivos, caníbales salvajes, animales o elementos naturales, o víctimas de explotación. La “otredad” de la Amazonía y los amazónicos se elaboró a través de un discurso de oposiciones binarias que retrataba a los hombres blancos occidentales como exploradores y explotadores que dominaban la pantalla, los guiones, los estudios y los proyectos de desarrollo, incluso si estos estaban condenados al fracaso. Al confiar en un sistema simbólico de diferencia basado en oposiciones binarias y estereotipos, la cobertura mediática global y las películas sobre la Amazonía en la década de 1970 fungieron como cómplices en la legitimación de los tipos de proyectos y políticas llevados a cabo en la región. © 2021 Latin American Perspectives.
Keywords: amazonie; amériques; approches et analyses; brésil; discipline; domination blanche; domination masculine; histoire; histoire et politique; médias; peuples autochtones; projet charge mentale; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; violences coloniales; violences racistes; violences sexistes

Noires sous surveillance : esclavage, répression et violence d'État au Canada - Maynard, Robyn (Mémoire d'encrier, 2018)
La vérité a souvent un goût amer. Nous ne savons comment accepter nos histoires. Faut-il s’en tenir aux faits et dire la vérité ? Cet ouvrage monumental si richement documenté est précieux, il nous tire de l’oubli et du silence. Que savons-nous de l’esclavage au Canada ? Que savons-nous de la répression exercée sur les femmes et les hommes noirs ? Que savons-nous du racisme systémique ? Que savons-nous de la détresse des Autochtones, des sans-papiers, des personnes réfugiées ? Enfin fort peu… Parce que l’État construit et déconstruit les récits à travers les institutions. Les citoyen.ne.s sont ainsi condamné.e.s à reproduire une histoire qui nous échappe.
Donné en lecturecours FEM1000: "La misogynoire au Canada" p.173-178 Donné en lecture au cours POL4212: « Chapitre 5 : La Mysoginoire ».
Keywords: EDI; afro-féminisme; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; fem3300; féminismes noirs; histoire; justice sociale; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences

Un féminisme inclusif ? La Fédération des femmes du Québec et les femmes immigrantes ou racisées, 1966-1992 - Ricci, Amanda (Bulletin d'histoire politique, 2017)
Number: 3 https://www.erudit.org/fr/revues/bhp/2017-v25-n3-bhp03054/1039747ar/
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; discipline; histoire; histoire et politique; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Lessons in Self-Defense: Gender Violence, Racial Criminalization, and Anticarceral Feminism - Thuma, Emily (Women's Studies Quarterly, 2015)
Keywords: 1900-1999; 1980-1989; afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; féminisme autochtone; féminismes noirs; histoire; injustice; intersectionnalité; militance; patriarcat; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; résistance; sciences humaines; systèmes d'oppressions; thématiques; viol; violences; violences d'état; violences sexistes et sexuelles; états-unis; études de genres

Blanches et Noires : histoire(s) des Américaines au XIXe siècle - Lehuu, Isabelle (Institut de recherches et d'études féministes, 2011)
«Les chapitres qui suivent mettent en lumière tant la parole des femmes que le discours sur les femmes, les actions et les représentations. Ils explorent la réalité quotidienne de femmes ordinaires du XIXe, jeunes et moins jeunes, mariées et célibataires, blanches et noires, au Nord comme au Sud, qui sont restées silencieuses, souvent dans l’ombre d’un mari, d’un père ou d’un maître. Leurs témoignages, les mots qu’elles ont laissés dans les sources publiques et privées, les gestes qu’elles ont posés aussi bien dans le cadre de leurs relations affectives qu’au sein de leur exploitation familiale, leur réseau social, leur travail, leur église, leur communauté urbaine ou villageoise, leur région, sont autant d’indices à décoder pour dresser un portrait nuancé et documenter la condition des femmes aux États-Unis dans toute sa diversité sociale et culturelle.»
https://revues.uqam.ca/prefix/cahiers-iref/agora-no-2-2012blanches-et-noires-histoires-des-americaines-au-xixe-siecle/
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; black feminism; cours; discipline; esclavagisme; femmes* blanches; femmes* noires; féminisme afroaméricain; féminismes noirs; his4443; histoire; histoire des femmes*; intersectionnalité; justice sociale; militance; mouvement aboitionnisme; philosophie politique; premier cycle; privilèges; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; états-unis (sud); études féministes

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Femmes, race et classe - Davis, Angela Y. (Angela Yvonne) (Des Femmes-Antoinette Fouque, 2007)
Dans Femmes, Race et Classe, Angela Davis, historienne et militante, développe une analyse critique des liens parfois conflictuels ayant existé au cours des XIXe et du XXe siècles entre féminisme et luttes d’émancipation du peuple noir. Elle démontre que les luttes ont porté leurs fruits à chaque fois qu’elles ont été solidaires. Se refusant à mettre en concurrence les différents éléments constitutifs de sa propre identité, elle affirme que les oppressions spécifiques doivent être articulées à égalité pour dépasser les contradictions et mener un combat global contre le système capitaliste au fondement de toutes les exploitations. Cet essai dense et fondateur, écrit en 1980, trouve aujourd’hui une actualité centrale avec les débats contemporains sur le féminisme dit « intersectionnel ».
Première publication:1981
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; classe sociale; com5170; cours; cycles supérieurs; discipline; fem1000; fem9000; féminismes noirs; histoire; histoire et politique; incontournable; intersectionnalité; inégalités; lit3220; militance; mouvements sociaux; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (University of North Carolina Press, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Disponible en livre numérique et en format imprimé.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Peau noire, masques blancs - Fanon, Frantz (Seuil, 1971)
La décolonisation faite, cet essai de compréhension du rapport Noir-Blanc a gardé toute sa valeur prophétique : car le racisme, malgré les horreurs dont il a affligé le monde, reste un problème d'avenir. Il est ici abordé et combattu de front, avec toutes les ressources des sciences de l'homme et avec la passion de celui qui allait devenir un maître à penser pour beaucoup d'intellectuels du tiers monde.
Première publication: 1952
Keywords: 1900-1999; 1950-1959; amériques; antilles; approches et analyses; colonialisme; cours; discipline; décolonialisme; europe; fem1000; femmes* noires; france; féminisme décolonial; har4600; histoire; postcolonialisme; premier cycle; psychanalyse; périodes historiques; racisme; régions géographiques; sciences; sciences humaines; systèmes d'oppressions